Quantification and normalization of training loads by using the criterions of exercise pulse cost - Volkov, N.; Popov, O.; Voitenko, Y. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Adaptation to influence of physical loads in sports training may be quantitatively described by relationship "dose-effect" . The value of trained function increase for the period of observation is assumed as a parameter of achievable effect. A dose of influence of physical load is defined as the product of intensity of exercise energy expenditure on the period of the physical load action. The energy cost in exercise can be estimated on the basis of direct recording of metabolic shifts at physical work, and also by an exercise pulse cost derived from the analysis of heart rate change dynamics during work and recovery (Volkov et all 2005). Methods: 26 well-trained male swimmers, middle-distance runners and skaters (age 18-24 years, height 162-186 cm, body mass 62-83 kg), ranging from club to international level, volunteered to take part in the study. All subjects performed 5 all-out tests - 10 s, 30 s, 60 s, 120 s and 360 s duration without preliminary warm-up. The gas volume, the O2 and CO2 fractions in the expired air were measured using a monitor system (Meta-Laizer 3B-R2, Cortex, Germany). O2-intake, O2-debt, O2-requirment, aerobic and anaerobic energy output were calculated with a special computer program. The blood lactate concentration is determined using an enzymatic method Dc Lange. Acid-alkaline balance parameters were determined using a pH and blood gases microanalyzer (AVL-800, Radiometer, Denmark). Results: Changes of parameters total pulse cost in dependence with values of exercise limiting time close reproduce appropriate relationships for parameters oxygen requirement and energy cost of exercise. Thus, pulse cost indices may be used as objective criteria for quantification physical loads as well at the development of programs of optimization of training in various kinds of sports. In exercises 10- s duration power was 850 (108) W, pulse cost of exercise 222 (59) beats, oxygen requirement rate 32.4 (5.2) l min(-1), maximum lactate accumulation 8.63 (1.93) mmol l (-1). In exercises 60-s duration the corresponding data were 380 (37) W, 450 (136) beats, 11.01 (1.28) l min(- 1), 15.11 (0.96) mmol l (-1). In exercises 3-min duration the corresponding data were 170 (14) W, 870 (182) beats, 4.4 (0.34) l min(-1), 15.67 (1.49) mmol l (-1). As a criteria of achived training effect is used a increase of physical performance and as a criteria of physical load dose is used a product of relative power and total pulse cost of exercise. Conclusions: Calculations of exercise pulse costs allow precise and specific selection of training loads for each athlete. The standards for training and competition loads based on parameters of exercise pulse cost should be defined differentially for athletes specializing in different sports with different training regiments.